The Use of Complementary and Alternative Medicine in Turkish Patients with Rheumatic Diseases - Hasan ULUSOY; Tülün Kaya GÜÇER; Murat AKSU; Şule ARSLAN; Abdülkadir HABİBOĞLU and Gürkan AKGÖL and Ayhan BİLGİCİ and; KURU and; n ÇETİN and Ayhan KAMANLI and et al. (Archives of Rheumatology, 2012)
Objectives: The aim of this study was to determine the prevalence of complementary and alternative medicine (CAM) use, to define the most frequently used CAM methods in rheumatic diseases, as well as to assess resources of information encouraging patients using CAM, and to evaluate the physicians’ attitudes toward CAM use. Patients and methods: We conducted face-to-face interviews with 318 patients with rheumatic diseases (212 females, 106 males; mean age 48.0±15.1 years; range 18 to 79 years) regarding demographic variables, history of CAM use, preferred CAM methods and resources of information encouraging patients using CAM. Complementary and alternative medicine methods were categorized as follows; 1- Acupuncture, 2- Biofeedback, 3- Dietary modifications, 4- Body-based practices, 5- Magnetic or copper devices, 6- Behavioural methods, 7- Others. Results: Approximately half of the patients (46.2%) experienced at least one method of CAM previously. The most frequently used methods of CAM were dietary modifications (28.9%) and body-based practices (16.4%). Patients with non-inflammatory diseases used CAM more frequently compared to the patients with inflammatory diseases (p=0.023). While 26.5% of the users were satisfied with the benefits of CAM, 73.5% believed that CAM was inadequate or useless. Most of the patients using CAM were encouraged by their relatives and mass media, whereas only 13.6% used CAM with the recommendation of their physician. One half of the physicians were indifferent in respect of CAM use. Conclusion: Complementary and alternative medicine methods are commonly used among patients with rheumatic disorders. However, unfortunately, the most frequent resources of information on CAM are patients’ relatives or mass media, rather than a health care professional. Therefore, physicians should be equipped with sufficient knowledge to inform their patients extensively on the use of CAM methods.